MEDIATING ROLE OF EMOTIONAL LOYALITY IN ONLINE DONATION - Hendrika Kenang, Irantha; Chester Somangkey, Gerald; Laurensia Soetandio, Linda (Jurnal Keuangan dan Bisnis, 2023)
Donating behavior has experienced a shift from conventional to digital. To ensure the continuity of donations, companies are required to have a strategy to attract and retain donors. This study aims to analyze platform trust in online donation platforms and emotional loyalty as factors that influence the continuation of donating to online-based donations. Attachment theory is used as a basis in this research where this theory states that strong emotional attachment creates loyalty that can prevent discontinuity in the use of products or services. Then, quantitative measures were used by distributing questionnaires to the selected sample, and 166 responses were collected. The data were analyzed using SEM. The results show that platform trust has an effect on emotional loyalty and continued intention to donate and emotional loyalty has an effect on the continued intention to donate, as well as being a partial mediating variable.